PENERAPAN MODEL PEMBELAJARAN KOOPERATIF METODE GIVING QUESTION AND GETTING ANSWER DALAM PEMBELAJARAN FISIKA PADA SISWA KELAS VIII-A SMP NEGERI 10 BANDA ACEH - Khali Jannah (JURNAL FISIKA EDUKASI, 2015)
This research is to reveal the effectiveness of the implementation of learning physics using cooperative learning methods giving the question and getting the answer the subject of optical devices on a eighth grade students of SMP Negeri 10 Banda Aceh, an increase or change in learning physics, physics learning outcomes and student response. The subjects were students of class VIII-A of SMP Negeri 10 Banda Aceh was 22 people in the second semester of 2013/2014 study year. Object of this research is the application of cooperative learning method, giving the question and getting the answer. This study is a collaborative action research conducted in 3 cycles. Each cycle consists of phases of planning, implementation, monitoring and evaluation, and reflection. Data collection instruments used in this study include: test and non-test forms. Results obtained as follows: (1) the implementation of learning physics in Class VIII-A subject of optical devices by implementing cooperative learning methods giving the question and getting the answer is more effective in terms of time as well as the achievement of student learning outcomes, and favored students, (2) improvement or changes that occur during the learning process associated with learning how to better direction after the applied method of giving the question and getting the answer. (3) the response of students towards learning physics is taught by implementing cooperative learning methods giving the question and getting very positive show